At the edge of Camelot : debating economics in turbulent times - Katzner, Donald W., 1938- (New York ; Oxford : Oxford University Press, 2011)
Donald Katzner tells the story of an academic department that underwent rapid, wrenching changes from the late 1960s through the 1970s. The story told covers the particulars of the background for these events relating to the University of Massachusetts, the political activism of the period, and the state of the economics profession.
Includes index.
Description based on print version record.
Keywords: University of Massachusetts at Amherst. -- Economics Dept. -- History; Economics -- Study and teaching (Higher) -- Massachusetts -- Amherst -- History